1060 Tackling child inequality in a UK Emergency Department: a pilot early intervention service on the shop floor. (17th August 2022) - Dor, Fahmida; Wright, Katie; Dutton, Fran; Willoughby, Robert; Bird, Christopher
Abstract : Aims: Around 30% of children and young people (CYP) live below the official poverty line. Exacerbated by the pandemic, spending on preventive early interventions declined by 48% in the UK over the last decade, while expenditure on youth justice services, safeguarding and children in care increased by 34% in the same period.(1) Child poverty has toxic effects, including: infant death; low birthweight; bottle feeding and tooth decay; second hand smoke exposure; obesity; asthma; poor school performance; and death in an accident.(2) The Emergency Department at Birmingham Children's Hospital, with 60, 000 annual attendances, serves the UK's diverse second city where 51% of CYP live in the 10% most deprived areas in England. The Early Help scheme aims to prevent children and families needing more specialist services, helping with housing, finance, food poverty, digital exclusion, mental health, child development, SEND and many others. The pilot service based in the ED was introduced to raise awareness of Early Help among ED staff and to increase support to attending families with barriers to health and social care. Methods: An Early Help coordinator (FD) began work alongside ED clinicians from 1 st November 2021 with the aim of bringing Early Help to children and their families attending the ED. Alongside referrals made to Early Help the pilot plans to evaluate any reduction in referrals to specialist services. Out of hours, referrals are still made and picked up the next working day. Results: In the first three months (Nov 2021-Feb 2022), 150 referrals were made to Early Help from ED nursing and medical staff, where none had been made previously. These resulted in 60 Family Connect Forms (assessments) completed across Birmingham (and a further 16 out of area) while 74 Early Help conversations took place (advice). Common referrals centred on: temporary accommodation; homelessness; poor and overcrowded living conditions; financial difficulties; food parcels; parenting support; children with learning needs; education. The Early Help service found four main themes: poor housing (effecting physical and mental health) inadequate support provided by stretched social services to families with children with life limiting conditions and disabilities large number of CYP presenting to ED with mental health issues not meeting the threshold for mental health services families missed by under-resourced Health Visiting services (resulting in missed diagnoses of developmental delay) Conclusion: The pilot has been overwhelmingly positive for the ED, with the Early Help coordinator ensuring struggling families are directed to the support they need; guiding clinicians through the complexities of support; enabling ED referrals to Early Help that were not made previously, leading to greater awareness of how inequality determines health outcomes. The pilot has been extended, with plans to base members of the hospital safeguarding team alongside Early Help in the ED. References: Williams M, Franklin J. Children and young people's services: Spending 2010-11 to 2019-20. 2021 Jul. Wickham S, Anwar E, Barr B, Law C, Taylor-Robinson D. Poverty and child health in the UK: using evidence for action. Archives of Disease in Childhood. 2016 Aug;101(8):759–66.